(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To assess and compare the actual responsibilities of pharmacists in the inpatient medication review process at 108 Military Central Hospital with current legal regulations, thereby proposing a revised medication review procedure that meets both professional requirements and practical needs. Subjects and methods: This qualitative study was conducted from December 2024 to February 2025 at the Department of Pharmacy and the Institute of Gastroenterology – 108 Military Central Hospital. Data were collected through direct observations and semi-structured interviews with nine healthcare professionals and analyzed using thematic coding with independent cross-review. Results: The current pharmacist-led inpatient medication review mainly focuses on administrative verification. Due to limited staffing and time constraints, pharmacists are unable to review each medical record thoroughly, thus falling short of fulfilling their clinical responsibilities as prescribed by existing regulations. Error detection relies heavily on personal experience, lacking support tools and interprofessional collaboration. Proposed improvements include increasing staff, assigning pharmacists by specialty, refining the review workflow, and applying technology to enable case-by-case review immediately after prescribing, with digital documentation of interventions. Conclusion: Pharmacists are not yet fully performing their mandated duties in inpatient medication review, facing significant limitations in human resources, clinical expertise, and technological support. Strengthening both the quantity and quality of pharmacy personnel and implementing a revised medication review process are essential to ensuring pharmacists can fulfill their roles in improving the safety, rationality, and effectiveness of inpatient medication use.